Efficient Ternary Polymer Solar Cells with Two Well‐Compatible Donors and One Ultranarrow Bandgap Nonfullerene Acceptor. Issue 11 (17th January 2018) - Ma, Xiaoling; Mi, Yang; Zhang, Fujun; An, Qiaoshi; Zhang, Miao; Hu, Zhenghao; Liu, Xinfeng; Zhang, Jian; Tang, Weihua
Abstract: Nonfullerene polymer solar cells (PSCs) are fabricated by using one wide bandgap donor PBDB‐T and one ultranarrow bandgap acceptor IEICO‐4F as the active layers. One medium bandgap donor PTB7‐Th is selected as the third component due to the similar highest occupied molecular orbital level compared to that of PBDB‐T and their complementary absorption spectra. The champion power conversion efficiency (PCE) of PSCs is increased from 10.25% to 11.62% via incorporating 20 wt% PTB7‐Th in donors, with enhanced short‐circuit current ( J SC ) of 24.14 mA cm −2 and fill factor (FF) of 65.03%. The 11.62% PCE should be the highest value for ternary nonfullerene PSCs. The main contribution of PTB7‐Th can be summarized as the improved photon harvesting and enhanced exciton utilization of PBDB‐T due to the efficient energy transfer from PBDB‐T to PTB7‐Th. Meanwhile, PTB7‐Th can also act as a regulator to adjust PBDB‐T molecular arrangement for optimizing charge transport, resulting in the enhanced FF of ternary PSCs. This experimental result may provide new insight for developing high‐performance ternary nonfullerene PSCs by selecting two well‐compatible donors with different bandgap and one ultranarrow bandgap acceptor. Abstract : Highly efficient ternary nonfullerene polymer solar cells (PSCs) are fabricated by employing two well‐compatible donors with complementary absorption spectra and one ultranarrow bandgap acceptor. The power conversion efficiency and short‐circuit current density of ternary PSCs are simultaneously increased to 11.62% and 24.14 mA cm −2 by incorporating 20 wt% PTB7‐Th due to the enhanced photon harvesting and optimized film morphology.